Good Corporate Governance as a Moderator of Tax Planning, Profitability, and Firm Value in Food and Beverage Companies - Bunga Fitaloka; Bani Binekas (Jesya, 2026)
The purpose of this study is to investigate the impact of Good Corporate Governance as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange, as well as the implications of tax planning and profitability on firm value. The motivation for this study stems from earlier research on the impact of profitability and tax planning on firm value, which produced mixed results. The research uses a quantitative methodology with descriptive-causal features. The secondary data used came from the financial statements and annual reports of companies in the food and beverage industry that are listed on the Indonesia Stock Exchange. Multiple linear regression and Moderated Regression Analysis (MRA) were used in the data analysis process to examine the direct and moderating effects between the variables. The findings show that firm value is positively and significantly impacted by profitability, indicating that firms with higher profitability levels typically have higher firm value. On the other hand, firm value is not much impacted by tax planning. Additionally, neither the relationship between profitability and firm value nor the association between tax planning and firm value is moderated by good corporate governance. Nonetheless, it has been demonstrated that firm value is directly and significantly impacted by sound corporate governance. These results show that, without enhancing the impacts of tax planning or profitability on firm value, the application of sound corporate governance contributes to a direct increase in firm value.